Kreativitas Versus Dehumanisasi Seni Desain: Keterampilan Manusia di Tengah Tantangan Kecerdasan Buatan dalam Era Digital - Zuharmando Ghaffara, Muhammad; Dede Pramayoza; Asril (Besaung : Jurnal Seni Desain dan Budaya, 2025)
This article examines the significant changes experienced by digital design artists in the era of artificial intelligence (AI), especially related to transformations in the creative process, originality and human values ​​in art. The main problem of this research is that the current development of AI technology with all its advances can create works of art quickly and with high quality, which previously could only be done by artists. This raises concerns among artists regarding the potential for commodification of works of art, loss of emotional elements and a decrease in the value of originality due to automatic processes that are less personal. But on the other hand, AI also opens up new opportunities in artistic exploration, allowing artists to integrate traditional techniques with technological innovations to speed up the creation process. Through a qualitative descriptive approach, the main aim of this research is to investigate artists' views regarding the use of AI, both as a partner and as a threat. The analysis results show that AI influences the role and identity of artists, especially in maintaining emotion and meaning in digital art. It is hoped that these findings can provide an understanding of the balance between technology and human expression in art, as well as answer ethical and aesthetic challenges in the context of art that continues to develop.